Prediction of cementitious composite characteristics based on waste glass powder and aggregates: Experimental and statistical analysis - Mezaouri, Sarra; Mamoune, Sidi Mohamed Aissa; Siad, Hocine; Lachemi, Mohamed; Boumaaza, Messaouda; Belaadi, Ahmed; Alshaikh, Ibrahim M.H.; Ghernaout, Djamel; Chetbani, Yazid; Laouissi, Aissa (Elsevier B.V., 2025)
The studys objective is to examine the influence of the use of waste glass powder and aggregate in maximum quantities on the characteristics of cementitious composites to create an environmentally friendly mortar with good mechanical strength. This concept is in line with circular economic principles by repurposing waste materials, reducing landfill usage, and minimizing environmental impact. Waste glass aggregate (WA) has been used to replace standardized sand at proportions of 0%, 25%, 50%, 75% up to 100%. Furthermore, waste glass powder (WP) has been used to replace cement in proportions of 0%, 5%, 10%, 15%, 20%, 25% and 30%. The experimental procedure was conducted and evaluated utilizing response surface methodology (RSM), and an analysis of variance (ANOVA) approach was employed to detect the parameters (WA and WP) that most influenced the measured responses, such as 360-day compressive strength, greenhouse gases (CHGs), and energy. ANOVA for all mortar properties studied indicated that quadratic models predicted effectively, with an R2 coefficient of determination near 1. Multi-objective optimization based on empirical models derived from RSM identified optimal solutions for mortar properties, namely 92% WA replacement by natural aggregates and 19% WP content by OPC substitution. Experimental validation confirmed these predictions, with errors below 8%. Energy Dispersive X-ray spectroscopy (EDX) and Scanning Electron Microscopy (SEM) serving to confirm this conclusion.